Why Do Indonesian Adolescent Boys Have Poorer Schooling Outcomes than Girls? - Muller, Noel (World Bank, Washington, DC, 2019)
Indonesian secondary students perform worse academically than their peers in other countries, especially boys. In the 2015 Program for International Student Assessment (PISA) tests, Indonesia ranked among the worse of the 72 participating countries. More than half of 15-year-olds could read a text but could not answer simple questions related to it; that was only the case of 14 percent of students in high-performing Vietnam and 20 percent in member countries of the Organization of Economic Cooperation and Development (OECD). While Indonesian boys and girls had similar average scores in math and science, girls outperformed boys in average scores of reading.